Association Between Loyalty to Community Pharmacy and Medication Persistence and Compliance, and the Use of Guidelines-Recommended Drugs in Type 2 Diabetes. Issue 27 (July 2015) - Dossa, Anara Richi; Grégoire, Jean-Pierre; Lauzier, Sophie; Guénette, Line; Sirois, Caroline; Moisan, Jocelyne; Gogovor., Amede
<x xml:space="preserve">Abstract</x> Abstract Pharmacists record data on all drugs claimed and may build a personal relationship with their clients. We hypothesized that loyalty to a single pharmacy could be associated with a better quality of drug use. To assess the association between pharmacy loyalty and quality of drug use among individuals treated with oral antidiabetes drugs (OADs). This is a cohort study using Quebec Health Insurance Board data. Associations were assessed using multivariable logistic regression. New OAD users, aged ≥18 years. Individuals who filled all their prescription drugs in the same pharmacy during the first year of treatment were considered loyal. During year 2 of treatment we assessed 4 quality indicators of drug use: persistence with antidiabetes treatment, compliance with antidiabetes treatment among those considered persistent, use of an angiotensin-converting enzyme inhibitor or of an angiotensin II receptor blocker (ACEi/ARB), and use of a lipid-lowering drug. Of 124, 009 individuals, 59.75% were identified as loyal. Nonloyal individuals were less likely to persist with their antidiabetes treatment (adjusted odds ratio = 0.89; 95% CI: 0.86–0.91), to comply with their antidiabetes treatment (0.82; 0.79–0.84), to use an ACEi/ARB (0.85; 0.83–0.88) and to use a lipid-lowering drug (0.83; 0.80–0.85). Quality of drug use decreased as the number of different pharmacies increased (linear contrast tests <0.001). Results underscore the important role pharmacists could play in helping their clients with chronic diseases to better manage their drug treatments. Further research is needed to determine to what extent the positive effects associated with pharmacy loyalty are specifically due to pharmacists.